PENGARUH KEBIJAKSANAAN KREDIT TERHADAP PIUTANG PADA HOTEL RAMADA BINTANG BALI RESORT KUTA BALI - Ida Ayu Agung Ngurah Indrawati (Institut Pariwisata dan Bisnis Internasional, 2014)
Credit sales in hospitality industry is a strategy to increase sales and eventually increase profit. This strategy contains risks can not be uncollectible receivables due from credit rule which includes credit period, credit standards, collection of receivables wisdom, wisdom pieces, and conditions of economic activity and the level of credit monitoring is thought to affect doubtful accounts. This study tried to determine the effect of credit policy towards bad debts at Ramada Bintang Bali Resort Tuban. The results showed the effect of the credit period for doubtful accounts is based on linear regression analysis is to have a relationship or a positive effect, which means the onset of bad debts caused by the hotel management continue to loosen credit policy given to customers. Determination analysis results showed the level of influence of the credit period to the ups and downs of bad debt amounted to 26% while the remaining 74% is influenced by other factors. Given the influence of a positive credit period and the rise and fall of the bad debt, then the company should pay attention and lending policies provide for sanctions subscription flowers that do not pay their obligations at a specified time limit.